Biosorption Of Copper Using Immobilised Eucheuma Cottonii Sp.Biomass Using One-Factor-At-Time (OFAT) - Hadi Afifi, Sulaiman (2023)
A type of industrial effluent that is frequently created by chemical waste, manufacturing, sewage, electroplating, and mining is heavy metal, also referred to as toxic metal. Heavy metal removal from wastewater may be done at a reasonable cost via biosorption. In order to remove heavy metals from industrial effluent, immobilised Eucheuma Spinosum sp., sometimes known as red seaweed, has been used as a biosorbent. Biosorbent made from immobilised seaweed has been used to remove heavy metals from industrial effluent. Heavy metal removal from wastewater may be done at a reasonable cost via biosorbent. This study aims to evaluate the first contact time, dose, starting pH, and initial concentration of the zine removal. The synthetic wastewater was created by dissolving 150ml Copper 1000mg/l in 1L of distilled water to create a 1000 mg/L Cu2+ solution. It is determined how much Cu originally existed in synthetic waste. After being immobilised, the seaweed was cleaned with distilled water. While the mixture is still being mixed, 0.25g of seaweed powder is added. The mixture was then injected into a 3g calcium chloride solution using a syringe. After that, distilled water was used to wash the treated alginate beads before they were changed into Calcium Chloride CaCI2. Following that, blend and let it cool to room temperature. Next, initial contact time, dosage, and initial concentration are examined in relation to the effectiveness of immobilised seaweed as a biosorbent. The biosorbent's weight is determined both before and after drying. Maximum removal of Cu took place with in 30 minutes for the immobilised seaweed. Meanwhile for the raw seaweed is 10 minutes, respectively. Further dosages had substantial absorption, with a starting absorption rate of 92.08% at 0.1g. When the influence of contact time is included, the elimination rate is 88% and 89% between 5 and 40 minutes. In concluded, biosorption using Euchuema Cottonii might be the best decision making for removal copper in wastewater compared to raw Euchuema Cottonii.